Ageing PSA incorporating effectiveness of maintenance and testing. (July 2015) - Martón, I.; Sánchez, A.I.; Martorell, S.
Abstract: This paper proposes a new approach to Ageing Probabilistic Safety Assessment (APSA) modelling, which is intended to be used to support risk-informed decisions on the effectiveness of maintenance management programs and technical specification requirements of critical equipment of Nuclear Power Plants (NPP) within the framework of the Risk Informed Decision Making according to R.G. 1.174 principles. This approach focuses on the incorporation of not only equipment ageing but also effectiveness of maintenance and efficiency of surveillance testing explicitly into APSA models and data. An example of application is presented, which centres on a critical safety-related equipment of a NPP in order to evaluate the risk impact of considering different approaches to APSA and the combined effect of equipment ageing and maintenance and testing alternatives along NPP design life. The risk impact of the several alternatives is quantified and the results shows that such risk depends largely on the model parameters, such as ageing factor, maintenance effectiveness, test efficiency. Highlights: New approach to Ageing Probabilistic Safety Assessment (APSA). Ageing, maintenance and testing addressed simultaneously and explicitly in APSA. APSA for Risk Informed Decision Making (RIDM) to support NPP Safety Review. RIDM on changes to maintenance management programs. RIDM on changes to surveillance requirements.